Dictionnaire de données des marques de commerce pour la norme XML ST.96 de l’OMPI - Office de la propriété intellectuelle du Canada (ISDE, 2018)

Juridictionnaire : Recueil des difficultés et des ressources du français juridique - Picotte, Jacques (Centre de Traduction et de Terminologie Juridiques, 2018)

Entrepreneurship in Africa - Akinyoade, Akinyinka; Dietz, Ton; Uche, Chibuike (African Dynamics, 2017)
Historically, entrepreneurs have always played a central role in the development of nation states. Aside from rentier states, which depend extensively on the availability of mineral resource rents, most economically prosperous nations in the world have strong, innovative and competitive business enterprises and entrepreneurs as the bedrock of their economic development and prosperity. It was arguably because of the above historical fact that the World Bank in 1989 declared that entrepreneurs will play a central role in transforming African economies. Chapters in this book contribute to our understanding of the theory, structure and practice of entrepreneurship in diverse African countries. Case studies examined include: African multinational banks and businesses, female entrepreneurs, culture and entrepreneurship, finance and entrepreneurship and SMEs.
Keywords: African Studies; Economic History; Economics & Political Science; History; Social Sciences; Sociology & Anthropology

Diccionario jurídico elemental - Molina, Ricardo Villa-Real; Torres, Miguel Ángel del Arco (Comares, 2014)
Con este diccionario ofrecemos una definición clara, precisa y rigurosa de los términos jurídicos más utilizados en la vida diaria y en los negocios. En cada definición encontrarás ejemplos prácticos y explicaciones didácticas sobre el uso correcto del término jurídico definido. Esto facilitará la comprensión de estos y permitirá saber cómo emplearlos correctamente tanto en una conversación cotidiana como en la práctica profesional.
Keywords: Diccionario; jurídico

Lexique des termes juridiques 2014 (Dalloz, 2014)

Lexique des termes usuels dans le transport maritime et liens utiles - Comité sectoriel de main-d'oeuvre de l'industrie maritime (Institut maritime du Québec, 2011)

Encyclopédie du droit OHADA - Pougoué, Paul-Gérard; Mercadal, Barthélémy; David, Jacques (Lamy, 2011)